Reconstruction of A Huge Soft Tissue Deffect in Flank Region Using Rectus Femoris Flap - Meirizal Hasan; Rahadyan Magetsari; Rezky Saraswaty (Journal of Global Pharma Technology, 2021)
Introduction:Coverage of full-thickness large flank defect is a challenging procedure for surgeons. The rectus femoris (RF) muscle flap is an excellent donor muscle for many reconstructions. The vascularized rectus femoris (RF) muscle flap has been proved to be effective to cover infected vascular grafts in the flank region. Outcome of the treatment can be evaluated by evaluating the patient daily activity. Case Report:This was a case report conducted on patient with huge soft tissue deffect in flank region. A 62 years old male with large defect of the right flank region due to infection of the abdominal cavity after appendectomy 2 months ago. The wound size 15 x 7 x 7 cm, with the base is bowel, with serohemoragic discharge. Then perform debridement and rectus femoris flap. A month after operation, the patient came to the Sardjito General Hospital with defect of the right hypogastric region and then VAC was performing in this patient. Two month after VAC, the wound was covered by granulating tissue and then the patient underwent FTSG. A month after the second operation, the patient came to outpatient clinic, able to walk, with the condition of the wound was good, no visible sign of infection. Conclusion:From this case report shows that rectus femoris flap has a good result to coverage the huge soft tissue defect in flank region. The patient can perform a simple daily living. Keywords: Rectus femoris, Flank defect, Flap.